Analisis Perbandingan Website Toko Buku Online Menggunakan Website Usability Evaluation Tool (Studi Pada Bukukita dan Tokopedia) - Lestari Fajrin Rohmah; Himawat Aryadita; Yusi Tyroni Mursityo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
E-commerce is one of proof of business development that happened in Indonesia. One of viable highlighted is the e-commerce book sales. Most of them, specially provide book buying and selling services. Others make the book as one of the items they offer. Bukukita and Tokopedia are one of each example. But both of those websites still do not have a maximum level of usability and there are still many shortcomings that reduce the user's convenience. This study compared the two websites in the aspects of usability in order to find out how the level of usability and which sites users easier. The evaluation of the two websites used a WEBUSE questionnaire consisting of: (1) content, organization, and readability, (2) navigation and links, (3) user interface design, and (4) performance and effectiveness. The samples were 17-25 year olds who have visited the Bukukita or Tokopedia website. The results of the evaluation showed that both websites were at usability good level and has no significant differences. Category of content, organization, and readability was category with the highest usability level on both web sites. While the category of performance and effectiveness was the category with the lowest usability level on both websites.